2015
DOI: 10.1111/1471-0307.12280
|View full text |Cite
|
Sign up to set email alerts
|

The role of exercise, milk, dairy foods and constituent proteins on the prevention and management of sarcopenia

Abstract: Sarcopenia, an age-related decline in muscle mass, is a burgeoning public health concern in the UK, with the number of people over the age of 65 expected to double by 2050. Resistance exercise is an effective intervention in its prevention and management. Increasing quantity and improving quality of dietary protein, by inclusion of high-availability leucine, are also purportedly beneficial. Leucine is a key anabolic amino acid, found in dairy foods. A number of studies have investigated dairy foods in preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(69 reference statements)
0
2
0
1
Order By: Relevance
“…Therefore, resistance exercises for 2-6 months (1 or 2 sessions per week) can significantly stimulate protein synthesis in the elderly. 22 Yarasheski et al indicated that after 3 months of resistance training with the exercise intensity of 65%-100% 1RM, the muscle mass increased. Consequently, the rate protein synthesis increases in older women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, resistance exercises for 2-6 months (1 or 2 sessions per week) can significantly stimulate protein synthesis in the elderly. 22 Yarasheski et al indicated that after 3 months of resistance training with the exercise intensity of 65%-100% 1RM, the muscle mass increased. Consequently, the rate protein synthesis increases in older women and men.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the regressions that developed for total and regional muscle conditions, we found that the presence of a higher amount of relative fat mass negatively influences SMM in both genders, with the regressions showing very similar standardized coefficients. The presence of hypertrophied adipocytes and the infiltration of macrophages in the adipose tissue generates the altered production of adipokines (reduced adiponectin and increased leptin, interleukin 6 and tumour necrosis factor-alpha), which translates into an inflammatory process at the muscle level and stimulates the infiltration of fat into the muscle [118].…”
Section: Connectedness To Nature and Body Compositionmentioning
confidence: 99%
“…O consumo diário de proteínas acima do mínimo indicado atualmente (0,8 g/kg/d) pode ser eficiente no sentido de manter a massa e função muscular em idosos (HOUCHINS et al, 2016;INSTITUTE OF MEDICINE OF THE NATIONAL ACADEMIES, 2005). Entretanto, apenas aumentar a quantidade de proteína na dieta diária de idosos não se mostra completamente eficiente, sendo necessário melhorar a capacidade de absorção dessas macromoléculas e a qualidade dos aminoácidos biodisponíveis, que são chaves para o anabolismo muscular (COOPER et al, 2016).…”
Section: 26unclassified